Visitors' books and registers in nineteenth-century Chamonix: ordering the sublime. Issue 3 (3rd July 2021) - Vincent, Patrick
ABSTRACT: A dense network of registers and albums existed in Chamonix, making it one of the most exemplary sites of nineteenth-century visitors' book culture. A significant number of these books have survived, enabling us to better understand the functions they served, and how they fit into the wider history of Chamonix's development. This was among other things a history of ordering, as the article shows in regard to the valley's historiography and to the development of its infrastructure. Focusing on travelogues and on several visitors' books and registers, the article examines how these books participated in these ordering processes.